Field efficacy and economics of newer insecticides against defoliators infesting castor (Ricinus communis L.): FIELD EFFICACY AND ECONOMICS OF NEWER INSECTICIDES AGAINST CASTOR DEFOLIATORS - M SENTHIL KUMAR; M JAYAKUMAR (Journal of Oilseeds Research, 2018)
Field experiments were conducted during kharif season of 2014-15 and 2015-16 to evaluate the field efficacy of newer insecticides emamectin benzoate 5WG @ 0.5 g/l, lufenuron 5EC @ 1 ml /l, flubendiamide 39.35 EC @ 0.2 ml/l, chlorantraniliprole 18.5SC@ 0.3 ml/l, lambda cyhalothrin @ 1 ml/l along with conventional insecticides like profenophos 50EC @ 2 ml/l, indoxacarb 14.5SC @ 1 ml/l, thiodicarb 75 WP @ 1 g/l against castor semilooper, tobacco caterpillar and hairy caterpillars in castor. The experiments were conducted in a randomized block design with eight treatments along with an untreated control and replicated thrice. The results revealed that the maximum percentage of larval reduction was in chlorantraniliprole 18.5 SC@ 0.3 ml/l followed by flubendiamide 38EC @ 0.2 ml/1. Highest seed yield of 1543 kg/ha was obtained from chlorantraniliprole treated plots, followed by that obtained with flubendiamide (1410 kg/ha) and profenophos (1375 kg/ha) treated plots with 93.5 and 88.7 per cent increase over control respectively as against minimum yield of 729 kg/ha in the untreated control. The favourable incremental cost-benefit ratio of 1: 6.25 was obtained with profenophos 50 EC @ 2 ml/l.